Cooper, Helen, and Robert R. Edwards, eds. 2023. The Oxford History of Poetry in English. Volume 2. Medieval Poetry: 1100–1400. Oxford: Oxford University Press. Pp. xxiii + 523. ISBN 9780198827429. - Scott-Macnab, David (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Cooper, Helen, and Robert R. Edwards, eds. 2023. The Oxford History of Poetry in English. Volume 2. Medieval Poetry: 1100–1400. Oxford: Oxford University Press. Pp. xxiii + 523. ISBN 9780198827429.